Effect of comprehensive cardiac rehabilitation after heart valve surgery (CopenHeart(VR)): study protocol for a randomised clinical trial - Sibilitz, Kirstine Laerum (BioMed Central, 2013)
BACKGROUND: Heart valve diseases are common with an estimated prevalence of 2.5% in the Western world. The number is rising due to an ageing population. Once symptomatic, heart valve diseases are potentially lethal, and heavily influence daily living and quality of life. Surgical treatment, either valve replacement or repair, remains the treatment of choice. However, post surgery, the transition to daily living may become a physical, mental and social challenge. We hypothesise that a comprehensive cardiac rehabilitation programme can improve physical capacity and self-assessed mental health and reduce hospitalisation and healthcare costs after heart valve surgery. METHODS: A randomised clinical trial, CopenHeart(VR,) aims to investigate whether cardiac rehabilitation in addition to usual care is superior to treatment as usual after heart valve surgery. The trial will randomly allocate 210 patients, 1:1 intervention to control group, using central randomisation, and blinded outcome assessment and statistical analyses. The intervention consists of 12 weeks of physical exercise, and a psycho-educational intervention comprising five consultations. Primary outcome is peak oxygen uptake (VO(2) peak) measured by cardiopulmonary exercise testing with ventilatory gas analysis. Secondary outcome is self-assessed mental health measured by the standardised questionnaire Short Form 36. Also, long-term healthcare utilisation and mortality as well as biochemistry, echocardiography and cost-benefit will be assessed. A mixed-method design is used to evaluate qualitative and quantitative findings encompassing a survey-based study before the trial and a qualitative pre- and post-intervention study. DISCUSSION: The study is approved by the local regional Research Ethics Committee (H-1-2011-157), and the Danish Data Protection Agency (j.nr. 2007-58-0015). TRIAL REGISTRATION: ClinicalTrials.gov (http://NCT01558765).